Analysis of Baganyi Tradition in the Perspective of Munakahat Jurisprudence: Husband-Wife Conflict Resolution in Minangkabau Society - Rahmi, Yulia; Firdaus, Beni; Yenti, Endri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to examine the baganyi tradition from the perspective of fikih munakahat, with an emphasis on social and legal dynamics in Minangkabau culture. The initial aim is to understand how baganyi affects the position of wives and children and how Minangkabau customs apply customary values with Islamic legal principles to resolve disputes within the family. This research uses a qualitative descriptive methodology by interviewing family members and looking at how Minangkabau families resolve conflicts. The results show that the baganyi tradition is a form of peaceful effort made by the women of the wife's family to return the husband who left home. This process involves several stages, starting from individual problem solving between husband and wife, then solving between two families with the help of ninik mamak and bundo kanduang. This research also found that the manjapuik sumando yang baganyi custom has a philosophy behind picking up the husband, which is to perfect or repair the rift in the husband-wife relationship. The implication of this research is the importance of integration between customary values and the principles of Islamic law in resolving husband-wife conflicts. Minangkabau custom with the baganyi tradition shows that the intervention of ninik mamak and bundo kanduang can help restore harmony in the household. It also shows that the status of the wife and children must be prioritized in the process of resolving husband-wife problems, so as to reduce the divorce rate and improve family welfare. Thus, this research contributes to a deeper understanding of the baganyi tradition and the importance of Minangkabau customs in overcoming marital problems, as well as its legal implications in the context of fiqh munakahat.